Phenomenologies of Religion - Brown, Laurence Binet (The international journal for the psychology of religion, 1991)
It is agreed that the multidimensional space that religions occupy has not been well described beyond its psychological basis in practice, belief, feelings or experiences, and consequential effects. The dependence of these elements on tradition-specific pressures and on the orthodoxies of scientific and religious methods and theoriesthrough which they have been systematized by Social scientistscould provoke and support a greater range of interpretation than is now current in understanding what is involved in carrying any religion.